Referral to pediatric ophthalmology: retrospective study of twelve months of referrals (Portuguese Journal of Family Medicine and General Practice, 2018)
The aim of this study was to evaluate the current state of the referral of children to the specialty of Ophthalmology at our Hospital-Centro Hospitalar do Porto, analyzing the reasons for referral, diagnosed diseases, effectiveness of referral and the visual impact on children.Methods: Retrospective and descriptive study of medical records of children aged ≤10 years-old referred to the Pediatric Ophthalmology Clinic, between July 2011 and July 2012.Results: A total of 649 children were referred and the most frequent reasons included suspected strabismus in 41.9%, screening for ocular pathology in 22.6%, and suspected low visual acuity (VA) in 15.2% of the cases. Amongst children referred for suspected strabismus, the diagnosis was confirmed in 40.8% of the cases (mean age of 4.5±2.2 years); 16.8% of children referred for other reasons also had strabismus. 62.3% were classified as esotropias and 32.3% as exotropias. Amongst the children referred for suspected low VA, the diagnosis was confirmed in 39% of the cases, and the main cause were ametropias (52% of cases). Of the children referred for other reasons, 13.3% had a measurable decrease in AV and 20% had potentially amblyogenic ametropias. Only 40% of the children referred by suspected low VA had a VA evaluation in the referral request. Amblyopia was diagnosed in 20.1% of all children observed. Discussion: The problems that most frequently motivated referral for pediatric ophthalmology were the suspicion of strabismus and of decreased VA. However, the diagnosis was confirmed in less than half of the referred children, and a significant percentage of diagnosed cases was referred for another reason. The mean age of diagnosis of strabismus was late, and the percentage of amblyopia was high. This study reinforces the importance of conducting ophthalmologic screening in primary health care, and its impact on a timely referral, diagnosis and treatment of these pediatric diseases.
Keywords: Referral; Strabismus; Ametropia; Amblyopia.